PEMUTUSAN HUBUNGAN KERJA DI SUATU PERUSAHAAN YANG TIDAK BERDASARKAN DASAR HUKUM YANG TEGAS - Fransiskus Xaverius Dias (Jurnal Paradigma Hukum Pembangunan, 2019)
Termination of Employment (PHK) is the termination of employment because something that results in the termination of rights and obligations between workers / employers and employers is regulated in Article 1 number 25 of Law Number 13 Year 2003 concerning Manpower. In termination of employment sometimes disputes arise. These disputes tend to occur because there is no common understanding between workers / laborers and employers regarding the termination of employment relations. Settlement of PHK disputes can be carried out by Bipartite, Mediation, Conciliation, Arbitration and the Industrial Relations Court. This study aims to find out how arrangements regarding layoffs associated with severe errors made by employees. The research method used in this study is normative juridical. Data sources used in the form of primary legal materials, secondary legal materials, and tertiary legal materials. The results showed that layoffs due to gross misconduct must not be carried out unilaterally by employers but must wait for the criminal justice process until a court decision has permanent legal force and states that the employee has been legally and convincingly proven to have made a serious mistake. The legal remedies that can be done by employees who are laid off are fighting through bipartite if bipartite fails then it can go through the court. The suggestion in this study is that a company should be in termination of employment (PHK) must comply with labor laws in force in Indonesia so that there are no parties who feel disadvantaged.